RESPON PENDENGAR PROGRAM MORNING MARKET DI RADIO MANDIRI FM PEKANBARU - Dedi Alpian; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Radio is a medium of mass communication are considered quite effective in delivering the message. Radio has become a very important part in the lives of people who are aware of the information. Mandiri FM radio is one private radio station in Pekanbaru that has several programs that gave the information to the needs of the community. Mandiri FM radio programs Morning Market which aims to inform about the food prices, traffic, flight at the airport Sultan Syarif Kasim II Airport in Pekanbaru directly inform the field. This study aims to determine the response of listeners to the radio program Morning Market, Mandiri FM Pekanbaru and how the process of presenting a program on Radio Morning Market Mandiri FM Pekanbaru.This research uses a qualitative methods with a descriptive approach. The research was conducted at the Radio Mandiri FM, Tuanku Tambusai street, 7th Pekanbaru with the object of study is the response of listeners in radio program Morning Market Mandiri FM, and the subject of the study is the entire informant who meet the research needs of the Program Manager Mandiri FM, announcer, reporter, and six programs listener Morning Market informant retrieval technique using purposive technique. techniques of data collection in this study using direct observation of spaciousness as well as in-depth interviews and documentation.The results of this study indicate that the first listener response to the Morning Market program, it is useful and necessary for listeners on the morning activities. Market Morning program to discuss three main topics on a daily basis that information about food prices, traffic and flight schedule information at the International Airport Sultan Syarif Kasim II Pekanbaru reported directly. Given the information on the listener program Morning Market traders helps them to know about the food prices as the market price of rice, meat, vegetables, fruits, for the avoidance of congestion and listeners know flight schedules. Both the process of presenting the Morning Market program on Radio Mandiri implemented through stages ranging from the determination of the location of the market, information retrieval and report directly connected to the studio.Keyword : Listener Response, Radio, Program Morning Market